Development of An AI-Assisted Instructional Video for The Schrodinger Equation in Modern Physics - Hilda Mazlina; Fitria Silviana; Melvi Maulida; Cut Rizki Mustika (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Learning Modern Physics, particularly the Schrödinger equation, often presents significant challenges due to the abstract nature of the concepts and the dominance of mathematical representations. These challenges were further intensified by the limitations of face-to-face instruction in post-disaster conditions in Sumatra, especially in Aceh. This study aimed to develop an AI-based Modern Physics instructional video designed to enhance conceptual visualization and narrative clarity of the Schrödinger equation while supporting students’ independent learning. The study employed a research and development approach involving 40 undergraduate students enrolled in a Modern Physics course at Universitas Islam Negeri Ar-Raniry. The instructional video was developed using artificial intelligence to strengthen conceptual visualization, integrate excerpts from popular films as contextual representations, and provide explanations through real-time digital pen annotations. In addition, the video was complemented by an AI-based conceptual assistant accessed with a QR code to support students’ self-directed learning. Data were collected through expert validation, student feasibility testing, and student response questionnaires. The results indicated that the developed instructional video was categorized as highly feasible and was perceived as accessible, engaging, and relevant for independent learning. The use of TikTok as a video distribution platform was found to be effective in addressing access limitations and network constraints. The findings suggest that AI-based instructional videos have strong potential as a flexible and adaptive learning support solution for Modern Physics education in post-disaster contexts.